Financial Literacy and Digital Payment System in Nepal - Bhim Kumar Thapa, (Nepalese Journal of Management Research, 2025)
This study examined the impact of financial literacy (FL) on the adoption of digital payment systems (DPS) in Nepal, with attitude (Att_DPS) toward DPS and social influence (SI_DPS) as mediating variables. The research aims to contribute to the development of policies that enhance financial inclusion and advance Nepal’s progress toward Sustainable Development Goals (SDGs) 4 (Quality Education), 8 (Decent Work and Economic Growth), 9 (Industry, Innovation, and Infrastructure), and 10 (Reduced Inequality).Using a quantitative research approach with explanatory research design and 399 individuals who answered a standardized questionnaire, The data was analyzed and the direct and mediated links between financial literacy and DPS usage evaluated using structural equation modelling using SmartPLS. The results further confirm the hypothesis that FL has a strong and positive direct effect on DPS acceptance and moderating indirect effect through attitude toward DPS. It showed that financial literacy is another driver that increases the likelihood of adopting the advanced technologies of making payments as well as cause earlier confidence and preparedness among the individuals. Surprisingly, measures of attitude toward DPS emerged as a particularly strong mediator. While positive and significantly associated with DPS adoption, the role of social influence was not to moderate the DPS adoption effect of financial literacy. This means that FL plays a significant role in the influence of DPS through people’s attitudes towards the technology more than through cultural factors and the changing infrastructure in Nepal.